Allelic frequencies of the hs1.2 enhancer within the immunoglobulin heavy chain region in Dayton, Ohio patients screened for celiac disease with duodenal biopsy. Issue 8 (August 2017) - Liu, Jing; Law, Rebecca A.; Koles, Paul G.; Saxe, Jonathan C.; Bottomley, Michael; Sulentic, Courtney E.W.
Abstract: Background: Genetic and environmental factors contribute to the development of celiac disease (CD), but specific genetic predisposing factors remain poorly understood. One candidate is allele 2 of the hs1.2 enhancer within the immunoglobulin heavy chain region. In humans, there are four possible alleles and a previous study of an Italian cohort demonstrated a significantly increased frequency of allele 2 in patients with CD. Aims: The purpose of the current study was to determine if a similar association between allele 2 and CD exists in an American population from Dayton, OH. Methods: Subjects were screened for CD via esophagogastroduodenoscopy with duodenal biopsy. All biopsies were microscopically scored using a modified Marsh-Oberhuber classification. DNA was isolated from patients' buccal cells for hs1.2 genotype analysis using PCR. Results: Unlike the Italian cohort, allele 2 frequency was not significantly different in patients with histopathologic evidence of CD compared to patients without such evidence. However, our patient population as a whole demonstrated a significantly increased allele 2 frequency when compared to that previously reported within diverse ethnic populations. Conclusions: Since our comparative control patients do not necessarily reflect a healthy control population, an overall increase in allele 2 may reflect an association between allele 2 of the hs1.2 enhancer and a spectrum of gastrointestinal disorders.